Hand Washing Compliance Among Surgeons and Physicians in Tertiary Care Hospital at Multan (Medical Forum Monthly, 2024)
Objective: To determine the Surgeons and Physicians compliance with the World Health Organization (WHO) prescribed five moments of hand hygiene.Study Design: Descriptive / cross-sectional StudyPlace and Duration of Study: This study was conducted at the Department of Community Medicine, NMC, Multan. from Dec.1, 2016 to Jan. 31, 2017.Material and Methods: Non-probability convenient sampling was in this study. Hand washing compliance was compared among Surgeons and Physicians. A survey was performed in all surgical and medical units of teaching institution to observe the hand washing compliance randomly according to the WHO five moments of hand hygiene. Semi-structured proforma was used to collect the data secretly without the knowledge of the personnel who were being observed.Results: The mean compliance among Surgeons and Physicians was very low, 14.33% and 6.11%, respectively. There was a strong association between surgeons and physicians regarding hand washing at 95% confidence level. (P< 0.00). Surgical wards sink to beds ratio was 1:24 and bar soap to beds ratio was 1:48. Medical wards sink to beds ratio was 1:33 and bar soap to beds ratio was 1:49. Alcohol-based hand gel or sanitizer was not available in both Surgical and Medical units during the study period. Conclusion: Hand washing compliance was very low among surgeons and physicians. The reasons for poor adherence to hand hygiene was non-availability of good numbers of wash basins and bar soap. There is a necessity for regular education, re-education campaign and provision of amenities for hand hygiene.